STRATEGIES OF THE SOUTH SULAWESI PROVINCIAL ELECTION SUPERVISORY AGENCY (BAWASLU) TO PREVENT ELECTION ADMINISTRATIVE VIOLATIONS - Devi Aulia Rahmayani; Muhammad Nur Yamin; Oky Nur Pratiwi Johansyah; Nina Agustina (Universitas Negeri Makassar, 2026)
The high level of administrative violations in elections shows the need for Bawaslu's active role as an election supervisory agency to design strategies to prevent administrative violations appropriately, especially in the South Sulawesi Province area. This study aims to determine the strategy of the Election Supervisory Agency (Bawaslu) of South Sulawesi Province in preventing election administration violations. This research uses a qualitative approach andproduces descriptive data. Data collection was used with observation, interview, documentation, and questionnaire distribution techniques. Data analysis techniques use SWOT analysis and conclusion drawing. The results of this study indicate that the strategy of the Election Supervisory Agency (Bawaslu) of South Sulawesi Province in preventing election administration violations has several supporting factors and internal and external inhibiting factors. Based on the results of the SWOT analysis, it can be seen that the strategy of the Election Supervisory Agency (Bawaslu) of South Sulawesi Province in preventing election administration violations is in quadrant III, which is turn arround, so that the strategic direction needed is W-O (weaknesses-opportunity) or minimizing weaknesses by taking advantage of existing opportunities. Therefore, researchers suggest that the South Sulawesi Provincial Election Supervisory Agency (Bawaslu) take alternative strategies, namely 1). Increase the program budget to support participatory supervision with the community, 2). Maximizing the election administration socialization program by increasing program optimization, 3) Reducing election administration errors by increasing supervision of political parties and candidate pairs, 4) Adding employees in the field of technology and information and providing education or training to existing IT employees, and 5) Bawaslu South Sulawesi Province needs to improve infrastructure to improve performance.